Building change: Resilience Engineering after ten years. (September 2015) - Nemeth, Christopher P.; Herrera, Ivonne
Abstract: Resilience Engineering (RE) has developed theories, methods, and tools to deliberately manage the adaptive ability of organizations in order to function effectively and safely. As the first peer-reviewed journal publication in the field, this special issue has three purposes: to provide the scientific and industrial communities with the opportunity to present current work in RE, to critically view RE׳s progress and contributions to research and practice, and to pose questions to stimulate thinking about RE׳s future. We propose three values for the RE field of practice: observation, analysis, and design and development. The special issue׳s content and viewpoints are not intended to provide conclusive answers, but rather to stimulate further inquiry and growth.